Peran Guru Bimbingan dan Konseling dalam Implementasi Kurikulum Merdeka Belajar - Febriella Fauziah; Firman Firman; Riska Ahmad (Keguruan, 2022)
The curriculum aims to improve and optimize students so that they can become graduates who can be adaptive, flexible and altruistic in the global labor market. The curriculum requires students to be able to utilize and master technology that continues to develop and advance according to the times. So that these changes also align with educational goals, especially curriculum adjustments which are now called the independent learning curriculum. An effective independent learning curriculum must reflect a philosophy of goals, objectives, learning experiences, instructional resources, and assessment. In order for the implementation of the independent learning curriculum to be effective, the teacher must be involved in the development process. In particular Guidance and Counseling (BK) teachers have an important role in success in school as an extension of the hand that can diagnose and identify the needs of students. BK teachers are required to be skilled in optimizing the effectiveness of learning and improving the quality of education using the most suitable learning approaches/methods for students. Implementation of the independent learning curriculum so that it becomes a guide that is relevant and right on target and requires BK teachers as implementers of the independent learning curriculum so that it runs effectively. In writing this paper, the author uses a descriptive qualitative research method using a library approach.